Another Decade of Marine Climate Change Experiments: Trends, Progress and Knowledge Gaps - Bass, Alissa; Wernberg, Thomas; Thomsen, Mads; Smale, Dan (Frontiers in Marine Science, 2021)
Anthropogenic climate change is a significant driver of change in marine ecosystems globally. To improve mechanistic understanding of the impact of climate-related stressors, experimental work on marine organisms has intensified in recent decades. A synthesis paper by Wernberg et al. (2012) established that Marine Climate Change Experiments (MCCEs) published from 2000-2009 were primarily laboratory-based and focussed on single stressors and individual focal temperate species. Using consistent methodology, we compared the 2000-2009 analysis to experiments published in the following decade (i.e. 2010-2019) to assess recent trends in MCCEs and to determine to what extent knowledge gaps and research priorities have been addressed. The search returned 416 papers, versus 110 from the 2000s, indicating considerable intensification of research effort and output. We found again that single species studies were most common, particularly with benthic invertebrates as model organisms, and that laboratory-based research comprised over 90% of all studies. However, multiple stressor experiments increased substantially, where tests for interaction effects between ocean acidification (i.e. increased pCO2) and warming were particularly common. Furthermore, a wider range of model species were studied and more community-level experiments were conducted in the 2010s compared with the 2000s. In addition, studies on behavioural responses, transgenerational effects and extreme climatic events increased markedly. These recent advances in MCCEs have undoubtedly improved understanding of how climate change will affect marine organisms and the communities and ecosystems they underpin. Going forward, biases in the type and distribution of model organisms should be addressed to enhance general understanding of responses to environmental change. Similarly, experiments should manipulate a greater number and range of climate and non-climate factors and increase the number of target organisms to increase realism. Finally, where possible, further research should be combined and contextualised with field-based experiments and observations to better reflect the complexity of marine ecosystems and yield more representative responses to ocean climate change.